Use of the ReSVinet Scale for parents and healthcare workers in a paediatric emergency service: a prospective study - Pablo Vásquez-Hoyos; Jhon Camacho-Cruz; Shirley Briñez; Jorge Alvarez; Victoria Leal; Licet Villamizar Gómez (BMJ Publishing Group, 2021)
Introduction Most scales for acute respiratory infection (ARI) are limited to healthcare worker (HCW) use for clinical decision-making. The Respiratory Syncytial Virus network (ReSVinet) Scale offers a version for parents that could potentially help as an early warning system.Objective To determine whether or not the ReSVinet Scale for ARI in infants can be reliably used by HCWs and parents in an emergency service.Methods A prospective study was done of infants with ARI who were admitted to a paediatric emergency room to assess the ReSVinet Scale when used by faculty (paediatric doctor-professors), residents (doctors doing their first specialty in paediatrics) and parents. Spearman's correlation and a weighted kappa coefficient were used to measure interobserver agreement. Internal consistency was also tested by Cronbach's alpha test.Results Overall, 188 patients, 58% male, were enrolled. A Spearman's correlation of 0.92 for faculty and resident scoring and 0.64 for faculty or resident and parent scoring was found. The weighted kappa coefficients were 0.78 for faculty versus residents, 0.41 for faculty versus parents, and 0.41 for residents versus parents. Cronbach's alpha test was 0.67 for faculty, 0.62 for residents and 0.69 for parents.Conclusion There was good correlation in the ReSVinet scores between health professionals when used in the paediatric emergency area. Agreement between parents and health professionals was found to be more variable. Future studies should focus on finding ways to improve its reliability when used by parents before the scale is used in the emergency room.